2009
DOI: 10.1016/j.cub.2009.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Motor Entrainment to Music in Multiple Vocal Mimicking Species

Abstract: The human capacity for music consists of certain core phenomena, including the tendency to entrain, or align movement, to an external auditory pulse [1-3]. This ability, fundamental both for music production and for coordinated dance, has been repeatedly highlighted as uniquely human [4-11]. However, it has recently been hypothesized that entrainment evolved as a by-product of vocal mimicry, generating the strong prediction that only vocal mimicking animals may be able to entrain [12, 13]. Here we provide comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
267
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(275 citation statements)
references
References 24 publications
6
267
1
1
Order By: Relevance
“…More generally, these results, along with recent work on rhythmic entrainment in animals (40,41), suggest that a number of perceptual and motor mechanisms providing the biological bases for human music may be shared with some other species and call for a reevaluation of long-held assumptions about the species-specific nature and origin of human musical preferences.…”
Section: Resultsmentioning
confidence: 94%
“…More generally, these results, along with recent work on rhythmic entrainment in animals (40,41), suggest that a number of perceptual and motor mechanisms providing the biological bases for human music may be shared with some other species and call for a reevaluation of long-held assumptions about the species-specific nature and origin of human musical preferences.…”
Section: Resultsmentioning
confidence: 94%
“…Although a recent study reported this ability in a variety of non-human species (Schachner et al, 2009), animals display a very limited form of the behavior. In contrast it is particularly easy for humans to achieve average synchronization to a metronome and this forms the basis of all music and dance.…”
Section: Sensorimotor Synchronizationmentioning
confidence: 99%
“…Many nonhuman animals have been found to use auditory periodicities to entrain their motor behavior to an underlying beat (Schachner, Brady, Pepperberg, & Hauser, 2009). What is the effect of auditory temporal regularities on humans?…”
Section: Abstract: Attention Entrainment Rhythm Memory Word Memorymentioning
confidence: 99%